PEMBUATAN NATA DE COCO DI DESA TANJUNG PERING, KECAMATAN INDERALAYA UTARA, KABUPATEN OGAN - Marieska Verawati; eka Lidiasari; Parwiyanti Parwiyanti; Friska S (Politeknik Negeri Sriwijaya, 2020)
One of the simple technologies that potentially improve communities’ family economy is nata de coco production and preservation. Through community service program activities, the community was introduced and demostrated on how to produce and preserve nata de coco. The activities was conducted on Tanjung Pering village, a village that currrently under the Sriwijaya University Fostered Village Program, that is located in the North of Inderalaya District, Ogan Ilir Regency, South Sumatra Province. This activity aimed to introduce, train and transfer knowledge about the technology especially for low skills house wives and young women during their spare time as part of women empowerment strategy. And also for community who live around the Sriwijaya University Campus as part of Tri Dharma Perguruan Tinggi or university devotion programm for community. It is hopping that by this activity, the participants gained knowledge and skills so they can independently produce nata de coco for increasing their family income. However, this empowerment activity still requires the involvement of all stakeholders in the framework of community empowerment both from the central, provincial and district governments and universities, among others through continued assistance in developing the skills of its human resources and institutions.